COMPARATIVE ANALYSIS OF PT DHARMA POLIMETAL TBK'S FINANCIAL PERFORMANCE BEFORE AND AFTER THE ACQUISITION OF PT TRIMITRA CHITRAHASTA: A STUDY ON LIQUIDITY, LEVERAGE, AND PROFITABILITY RATIOS (2022-2024) - Wawan Andi Saputra; Wihartari; Noviyati Husnul Khatimah; Nurariqa Ahmad; Nurul Fitriani; Nur Suci Anggraeni (RADJA PUBLIKA, 2025)
This study aims to analyze the differences in the financial performance of PT Dharma Polimetal Tbk before and after the acquisition of PT Trimitra Chitrahasta, which was carried out in 2022. The analysis focuses on three main financial ratios: liquidity (Current Ratio), leverage (Debt to Equity Ratio/DER), and profitability (Return on Assets/ROA). The research method used is descriptive quantitative with a comparative approach, where data is obtained from the company's annual financial statements for the period 2022–2024 published by the Indonesia Stock Exchange (IDX). The analysis technique is carried out by comparing the ratio values ​​before and after the acquisition to assess changes in the company's financial performance. The results show that after the acquisition, PT Dharma Polimetal Tbk experienced a significant increase in the liquidity ratio and a decrease in the leverage ratio, reflecting the company's improved ability to meet short-term obligations and healthier capital structure management. However, the profitability ratio (ROA) shows fluctuations with a downward trend in the last year, indicating that the effectiveness of asset utilization in generating profits is not yet fully optimal. Overall, the acquisition of PT Trimitra Chitrahasta has a positive impact on the financial stability of PT Dharma Polimetal Tbk, although its profitability requires improvement through asset optimization and operational efficiency.